2018
DOI: 10.3390/ma11112150
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Mechanical Properties in Al–Si–Cu–Fe–Mg Alloys with Various Processing Parameters

Abstract: In this research, various processing conditions were implemented to enhance the mechanical properties of Al-Si alloys. The silicon content was varied from hypoeutectic (Si-10 wt.%) to eutectic (Si-12.6 wt.%) and hypereutectic (Si-14 wt.%) for the preparation of Al-XSi-3Cu-0.5Fe-0.6 Mg (X = 10–14%) alloys using die casting. Subsequently, these alloys were hot-extruded with an optimum extrusion ratio (17:1) at 400 °C to match the output extruded bar to the compressor size. An analysis of the microstructural feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Two precipitate shapes are present; needle-like precipitates of Si, with a length of 55 ± 13 nm and thickness of 6 ± 1 nm, and rather spherical precipitates of 16 ± 3 nm in diameter which are thus likely Al 2 Cu-based precipitates. The increased precipitate density can be related to the solution treatment during the T6 regime in which the Si intercellular network dissolved; an increased Si content in Al matrix promotes the diffusion coefficient of Cu in aluminium [17].…”
Section: Temmentioning
confidence: 99%
“…Two precipitate shapes are present; needle-like precipitates of Si, with a length of 55 ± 13 nm and thickness of 6 ± 1 nm, and rather spherical precipitates of 16 ± 3 nm in diameter which are thus likely Al 2 Cu-based precipitates. The increased precipitate density can be related to the solution treatment during the T6 regime in which the Si intercellular network dissolved; an increased Si content in Al matrix promotes the diffusion coefficient of Cu in aluminium [17].…”
Section: Temmentioning
confidence: 99%
“…In this work, we will use an Al–Si alloy for study. The Al–Si series is the most important system of the Al alloys, because of its excellent castability, weldability, and superior wear resistance [29,30,31,32,33,34,35]. The content, size, scale, and distribution of the Si phase have been commonly believed to strongly affect the mechanical properties and castability of the alloys [36,37,38,39,40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied the Vickers microhardness, including Tillová, et al [5], who, studying the intermetallic phases in Al-Si recycled alloys presents a microhardness of 483 HV, in addition, Isadarea, et al [17] studied Mechanical Properties of 7075 Aluminum Alloy, they found for this alloy the microhardness of 201 HV, however, the microhardness of 567 HV for Al-Si-Cu-Mg-Fe extruded alloy was measured by the authors Ahn [18]. Though, some authors, Kubota [19] and Xu, et al [20] determined the microhardness of pure aluminum, around 50 HV.…”
Section: Vickers Microhardness Measurementsmentioning
confidence: 99%